Magnesium Therapy in Pre-eclampsia Prolongs Analgesia Following Spinal Anaesthesia with Fentanyl and Bupivacaine: An Observational Study - Tülay Özkan Seyhan (Balkan Medical Journal, 2014)
Background: Magnesium has anti-nociceptive effects and potentiates opioid analgesia following its systemic and neuraxial administration. However, there is no study evaluating the effects of intravenous (IV) magnesium sulphate (MgSO4) therapy on spinal anaesthesia characteristics in severely pre-eclamptic patients.